GENDER CHIEF EXECUTIVE OFFICER DAN CASH HOLDING - Hidayat, Taufik; Rahman, Annisaa (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. This study aims to examine the effect of the chief executive officer gender on cash holding.Research Method. This study is a quantitative study with the dependent variable cash holding and the chief executive officer gender as the independent variable. Cash holding is measured by cash and cash equivalents divided by total assets, while gender chief executive officer is measured by the dummy variable female or male CEOs. This research was conducted on all non-financial companies listed on the Indonesia Stock Exchange in 2017-2019, with total sample company of 1134 companies - years. The research data was sourced from annual reports and financial reports, and data analyszed using multiple linear regression.Research Result and Findings. The results of this study indicate that the gender of the chief executive officer has a significant positive effect on cash holding. These findings provide support for the theory that women tend to avoid risk (risk aversion) and lack confidence in the decision-making process compared to men so they tend to have policies to hold more cash, which the findings of this study are in line with precautionary motives.